Pengaruh Ekstrak Air Buah Nanas terhadap Ekspresi Caspase-3 dan Fragmentasi DNA Sel Adenokarsinoma Kolorektal WiDr - Pribadi, Sintin Khotijah; Budiani, Dyah Ratna; Pesik, Riza Novierta (Nexus Biomedika, 2014)
Background: Colorectal adenocarcinoma is the third most diagnosed neoplasm in the world. Many approaches have been taken for therapy, especially targeted therapy. However, the resistance event still occurs due to constitutive activation of intracellular signaling. In the other hand, pineapple fruit [Ananas comosus (L.) Merr.] has bromelain enzyme that can specifically influence intracellular signaling and not only lead to inhibit proliferation but also lead apoptosis induction in neoplasm cell. The purpose of this study was to elucidate the effect of pineapple fruit aqueous extract to caspase-3 expression and DNA fragmentation of apoptosis process in WiDr colorectal adenocarcinoma cells. Methods: This research was an experimental laboratory study with the post test only control group design. The samples of this research were WiDr colorectal adenocarcinoma cells divided into 6 groups: Negative control group, Positive control group with doxorubicin 5 Î¼g/ml and four Treatment groups with 270 Î¼g/ml, 202.5 Î¼g/ml, 135 Î¼g/ml and 67.5 Î¼g/ml of extract concentration, each. The samples were incubated for 48 hours in 37oC and 5% CO2. The caspase-3 expression was determined by cytologic score of samples stained with caspase-3 antihuman antibody. The DNA fragmentation was determined by 1% agarose gel electrophoresis. The cytologic score was analyzed by one way ANOVA test and LSD test. Result: The result showed that there was significant difference between Positive control group and the other groups (p=0.000), but there wasnât significant difference between the Negative control group and the Treatment groups (p>0.05). The result from electrophoresis showed that there wasnât DNA fragmentation in WiDr colorectal adenocarcinoma cells. Conclusion: The pineapple fruit aqueous extract did not increase caspase-3 expression and did not lead DNA fragmentation to WiDr colorectal adenocarcinoma cells for 48 hours of treatment. Keywords: pineapple fruit aqueous extract, WiDr colorectal adenocarcinoma cell, caspase-3 expression, DNA fragmentation Â